Neurocognitive profile associated with borderline personality disorder: building specific indices of executive function. - Lopez-Villatoro, Jose Manuel; Diaz-Marsá, Marina; Rico-Perez, Ana; Fernandez-Rodrigues, Veronica; Ayad-Ahmed, Wala; Galvez-Merlin, Alejandra; Carrasco, Jose Luis (Actas Espanolas de Psiquiatria)
Introduction: The objective of this work is the creation of specific indices of the different executive functions (EF), which allow a more complete understanding of the executive performance associated with borderline personality disorder (BPD) and not through isolated tests. Methodology: 118 patients with BPD and 81 controls were evaluated with a neuropsychological battery. Three indices of attention, memory and FE were created. The tests that make up the executive domain were grouped into four different executive indices: cognitive flexibility, planning, working memory, and response inhibition. The batteries for each domain were compared through the standardized batteries of the tests that comprised them. Results: The results showed differences in the memory, attention, and EF indices, as well as in the different executive indices of cognitive flexibility, planning, working memory, and response inhibition, between BPD patients and controls. Conclusions: This study has allowed the creation of four executive indexes, being the first to do so. These results established a neurocognitive profile of BPD characterized by executive-specific impairment of cognitive flexibility, planning, working memory, and response inhibition. These findings support that patients with BPD will benefit from the application of neuropsychological programs, especially focused on improving a certain EF, and lay the foundations for the investigation of the relationship between these specific executive deficits and certain clinical characteristics of BPD, such as different types of Impulsive behavior and different mentalization errors.